ByzRev 07.2025.058: Charikleia Diamanti, Late Antique Stamped Amphorae as Evidence for Imperial Policy.: The Halasarna Workshop, Cos Island. Oxfordshire: Archaeopress Publishing Ltd. 2024. - Grünbart, Michael (The Byzantine Review, 2025)
Charikleia Diamanti, Late Antique Stamped Amphorae as Evidence for Imperial Policy. The Halasarna Workshop, Cos Island. Oxfordshire: Archaeopress Publishing Ltd. 2024. V, 128 S. – ISBN 978-1-80327-857-8, 978-1-80327-858-2 (e-Pdf